Perancangan Desain Website VoksEat dengan Menggunakan Metode Prototipe - Wildan Holik; Kanaya Sabila Azzahra; Muhammad Ilham Nufajri; Wien Kuntari (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study aims to design the VoksEat website as a food delivery service platform targeted at students of the IPB Vocational School. The methodology employed is the prototype method, allowing iterative design based on user needs. The research process began with identifying requirements through interviews and observations, followed by creating an initial prototype using design tools such as Figma and testing the prototype to gather user feedback. Object-oriented modeling with the Unified Modeling Language (UML) approach was utilized to ensure a well-organized system structure, including diagrams such as use case, activity, and class diagrams. The results indicate that the prototype method is effective in producing a functional website design that aligns with user needs. The VoksEat website features ordering guides, restaurant recommendations, and an integrated order form that provides users with easy access. This study contributes to developing a locally-based digital solution to meet student needs and enriches the literature on applying the prototype method in web-based information system development.